Effect of dietary supplementation of phytochemicals on immunity and haematology of growing broiler chickens. Issue 4 (2nd October 2018) - Kamboh, Asghar Ali; Khan, Muhammad Ammar; Kaka, Ubedullah; Awad, Elmutaz Atta; Memon, Atta Muhammad; Saeed, Muhammad; Korejo, Nazar Ali; Bakhetgul, Manatbai; Kumar, Chandar
Abstract: The current study investigated the effects of phytochemicals genistein and/or hesperidin dietary supplementation on immunity and haematology of growing broilers. A total of 360 1-day-old broiler chicks (Arbor Acres, mixed sex) were randomly assigned to six treatment groups, namely T0, control; T1 and T2, supplemented with 5 and 20 mg of genistein and hesperidin; while T3, T4, and T5 diets contained 5, 10, and 20 mg of genistein + hesperidin (1:4) mixture, respectively, per kg of diet. The white blood cell count was significantly ( p < .01) increased in T1, T2, T4, and T5 compared with the control (T0) group. The haemoglobin concentration significantly ( p < .01) increased in the T5 group, while mean corpuscular haemoglobin concentration was significantly ( p < .05) higher in T4 compared with the T0 group. Antibody titres against Newcastle disease significantly ( p < .01) increased in T1, T2, T3, T4, and T5 compared with the T0 group. Similarly, all phytochemicals treated groups exhibited an increase ( p < .01) in antibody titres against Avian Influenza virus, as compared with the controls. At the same time, the supplemented groups had significantly ( p < .01) higher neutrophil adhesion rate and cutaneous basophil hypersensitivity test representing the cellular immune response than the controls. In conclusion, supplementation with both phytochemicals, genistein and hesperidin, positively influenced the immune parameters and haematological profile of growing broilers, thus might be considered as feed additives in broiler industry.